External Financing, Earnings Management and Audit Quality - Vernando, Andreas; Yohana , Denny; Khamainy , Arief Hidayatullah; Palupi, Indarti Diah; Fithria, Annisa (Universitas Muhammadiyah Surakarta, 2025)
This study investigates the relationship between external financing and accrual earnings management (AEM). In examining this association, this study distinguishes external financing through debt and equity financing, which are more associated with AEM. In addition, this study also explores how audit quality moderates this relationship. This study employed a sample of non-financial companies from 2015 to 2019. We find that external financing is positively associated with AEM. This positive association is more pronounced with debt financing rather than equity financing. In addition, this study does not find that audit quality can mitigate AEM motivated by external and debt financing. Our results are robust after examining another EM measurement, real earnings management (REM).